Increasing Customer Satisfaction with Quality Function Deployment Methodology Based on Service Quality Analysis - Vazry, Johan; Hidayat, Hidayat; Negoro, Pandu Yanuar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
One way to be superior to competing companies in the service field, especially customer satisfaction, is by analyzing service quality. Satisfied customers can increase their loyalty and have more trust in a company, so they can continue using its services. PT. XYZ is a company that offers logistics accommodation services; this research took the period from January 2023 to February 2024. It is known that the number of fluctuating customers tends to decrease. Apart from that, there were also several complaints submitted by customers, including products arriving late, inability to fulfill customer requests, delays in the delivery process, and top payments not being evenly distributed. This research used the Servqual and Quality Function Deployment (QFD) methodology. The Servqual method was carried out by distributing questionnaires to 95 respondents to identify the biggest gaps based on the dimensions of tangibles, reliability, assurance, empathy, and responsiveness, which was then carried out with a QFD analysis to determine the priority of corrective action. based on technical response. The research results show that the reliability dimension has the largest gap value, 0.21. A QFD analysis is carried out objectively to determine quality improvement based on technical responses obtained from customers' voices. In the QFD analysis, it is known that the priority corrective actions that must be taken are carrying out correct transaction recording, faster employee processes, increasing employee skills, increasing security, optimizing the system, and increasing availability. Keywords: Customer Expectations, Customers Satisfaction, House of Risk, Service Quality, Quality Function Deployment